Pinch analysis approach to short-term scheduling of batch reactors in multi-purpose plants - Foo, Dominic C. Y. (Animo Repository, 2007)
Current trends in the chemical process industries indicate the growth of a significant niche for flexible, multi-purpose plants producing relatively small quantities of high-value products. Batch processes are inherently more suited to such applications, and extensive research has been done on process scheduling in such plants using mathematical programming, heuristic or artificial intelligence methods. This work describes an alternative approach based on pinch analysis, which has been used since the 1970s for applications ranging from conservation of industrial utilities in process plants, to management problems in supply chains, financial planning and emissions control. AU these applications assume that valuable resources need to be allocated to different demands with both quantity and quality specifications. Pinch analysis is shown here to be applicable to visualizing and analyzing the scheduling and allocation of batch reactors in multi-purpose plants. Two specific types of problems are described. The pinch analysis approach is demonstrated using illustrative case studies. The pinch analysis approach allows for quick identification of processing bottlenecks and provides rules for subsequent detailed scheduling. Copyright © 2007 The Berkeley Electronic Press. All rights reserved.